CTNI-06. SINGLE-CENTER REAL-WORLD ANALYSIS ON CEREBROSPINAL FLUID IN PATIENTS WITH LEPTOMENINGEAL METASTASES OF NON-SMALL CELL LUNG CANCER - Zhen, Junjie (Neuro Oncol, 2020)
OBJECTIVE: To investigate the clinical values of real-world cerebrospinal fluid (CSF) examination in the diagnosis and prognosis of leptomeningeal metastases (LM) in the patients with non-small cell lung cancer (NSCLC). METHODS: The clinical manifestations of patients diagnosed with NSCLC-LM in Guangdong Sanjiu Brain Hospital from 2010 until 2019 and the results from the routine, biochemical and cytologic examinations of their CSF were analyzed retrospectively. Moreover, the effects of different indicators on the prognosis of patients were determined by survival analysis. RESULTS: Fifty-eight of the 80 patients underwent CSF examination, and the median values of the initial CSF pressure measured by lumbar puncture was 255mmH(2)O (60-350mmH(2)O). Tumor cells were found by the cytologic examination of CSF in 56 of the 58 cases (96.6%). The median levels of protein, glucose, chloride, lactate dehydrogenase (LDH) and carcinoembryonic antigen (CEA) in CSF were 0.4g/L (0–8.3g/L), 2.7mmol/L (0–11.9mmol/L), 120.7mmol/L (0–140.5mmol/L), 21.3U/L (0–221.5U/L) and 31.4ng/ml (0–784.2ng/ml), respectively. Sixteen patients underwent gene detection, and the results showed that there were 4 cases of wild type and 12 cases of mutation type. The survival analysis revealed that the median overall survival (mOS) after being diagnosed with LM, patients in LDH≤37U/L group and those in LDH >37U/L group were 8.0 months, 23.7 months and 4.6 months (P=0.039), respectively, which indicated that the LDH level in CSF was the independent prognostic factor for the survival. CONCLUSION: Using the cytologic examination of CSF in patients with LM to detect tumor cells is conducive to the early diagnosis of LM. The high CSF pressure in patients with LM is one of the reasons for the neurologic signs and symptoms. The gene mutations found in the CSF in some patients can be used to guide the further systematic treatment. The LDH level in CSF is the independent prognostic factor affecting the survival.